Primary pulmonary lymphoepithelioma-like carcinoma: A case report of pathological complete response (pCR) by neoadjuvant treatment. Issue 11 (19th March 2021) - Zhang, Liqin; Hao, Tairan; Wei, Yuqing; Dong, Mo; Xiong, Yuancheng
Abstract: Rationale: Primary pulmonary lymphoepithelioma-like carcinoma (PPLELC) is a rare subtype of non-small cell lung cancer (NSCLC). It is predominantly reported in East Asia and currently there is no standard treatment for this disease. We report a case of stage IV PPLELC that achieved pathological complete response (pCR) by neoadjuvant treatment. Patient concerns: The patient was a 46-year-old male who developed hemoptysis for about 20 ml of volume accompanied by cough and sputum after physical labor. Diagnoses: Contrast enhanced chest CT scanning showed occupation of left lower hilar area and left pleural effusion. Combined with medical history and auxiliary examination, the patient was formally diagnosed stage IV lymphoepithelioma-like carcinoma of the left lower lung (T3N0M1a pleura). Interventions: The patient was given Sintilimab combined with gemcitabine + nedaplatin chemotherapy (GP) regimen for four cycles with 3 weeks as a cycle, supplemented with antiemetics and stomach protection drugs to reduce chemotherapy-related side effects. Outcomes: After 4 cycles of treatment, the patient's left lung lesion has been markedly reduced and the left pleural effusion has also been significantly absorbed. Remarkably, surgical biopsies found no cancer cells in the lesion site and postoperative pathology showed complete pathological remission (pCR). Lessons: We reported a case of PPLELC that is sensitive to neoadjuvant treatment, showing excellent effectiveness and safety and achieving pCR.